Simulation of ultrasonic wave propagation as corrosion of reinforcing bar progresses - Ambrocio, Ronn Mikhail M.
Non-destructive evaluation techniques by ultrasonic testing are applied to illustrate the cross section of concrete. Using Liu and Weyers' model for concrete cracking due to the corrosion of reinforcing bars, ultrasonic wave propagation can be simulated. Reinforced concrete samples were created and subjected to accelerated corrosion for varying times. Samples were evaluated by ultrasonic testing and subjected to inspection and measurements in order to gain precise data for reinforcing bar corrosion. An illustration of the simulation of ultrasonic wave due to the progression of corrosion reinforcing bars can be generated using the program created.